REFRESHING CADRES ON THE IMPORTANCE OF IMMUNIZATION IN AN EFFORTS TO REDUCE MORBIDITY RATES IN INFANTS AND TODDLERS - Gustina, Irwanti; Mella Yuria; Legina Anggraeni (CV. Naskah Aceh, 2023)
Toddlers are the nation's children who are the next generation of the nation who must be prepared in terms of knowledge, skills and health. Diseases caused by infections generally have severe and dangerous impacts that can be caused, such as disability or even death. These dangerous impacts can be prevented if children are given immunizations. One of the government's indicators in achieving health levels is reducing morbidity rates. The purpose of immunization is to form immunity so that they are not easily infected by viruses that cause disease, because the baby's body has a low level of immunity so that it must immediately get protection from infectious diseases. The purpose of this community service activity is to increase cadre knowledge about the importance of immunization in infants and toddlers. From the results of the activity, it can be concluded that after measuring the level of knowledge about immunization, 97% of cadres were able to answer questions correctly.